The Influence of Sustainable and Transformational Leadership on Innovation Performance of MSMEs Mediated by Self-Efficacy - Ratih Anggraini; Evelyn Loo; Ferdinand Nainggolan (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the impact of sustainable and transformational leadership styles on innovation outcomes in Micro, Small, and Medium Enterprises (MSMEs) in Batam City. This study specifically investigates how these leadership approaches influence innovation performance, with a particular focus on their role in shaping employee self-efficacy as a mediating factor. Research Methodology: This study uses primary data gathered through a questionnaire administered to 300 respondents. The sampling method employed is purposive, targeting Micro, Small, and Medium Enterprises (MSMEs) based in Batam City that have been in operation for a minimum of two years. Results: The results indicate that both sustainable and transformational leadership have a significant positive effect on innovation performance. Additionally, both leadership styles significantly enhance employees’ self-efficacy. Conclusions: The findings also revealed that self-efficacy acts as a mediating variable, strengthening the relationship between leadership styles and innovation performance. Limitations: This study focused only on MSMEs in Batam City, limiting its generalizability. Contributions: This study contributes to the existing literature by integrating the roles of sustainable and transformational leadership with self-efficacy and innovation performance, specifically within the context of MSMEs in Batam City.